2020
DOI: 10.1016/j.jaci.2020.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Baseline sputum eosinophil + neutrophil subgroups’ clinical characteristics and longitudinal trajectories for NHLBI Severe Asthma Research Program (SARP 3) cohort

Abstract: Disclosure of potential conflict of interest: J. C. Celed on has received research materials from GSK and Merck (inhaled steroids) and Pharmavite (vitamin D and placebo capsules) to provide medications free of cost to participants in NIH-funded studies unrelated to the current work. The rest of the authors declare that they have no relevant conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 9 publications
1
21
2
Order By: Relevance
“…Inflammatory subtype of sputum may thus predict prognosis, as reflected by future need of ICS, of individual patients. These results have been repeated and confirmed by a series of evidence from Severe Asthma Research Program (SARP) (63,64). They consistently demonstrated that mixed granulocytic subtype is the most refractory inflammatory subtype, characterized by the lowest lung function, worse asthma control, increased symptoms, greater healthcare requirements, and further loss in lung function, suggesting cell to cell interaction or overlapping inflammatory pathways (63,64).…”
Section: Inflammatory Subtype and Future Maintenance Therapy/ Controlmentioning
confidence: 76%
“…Inflammatory subtype of sputum may thus predict prognosis, as reflected by future need of ICS, of individual patients. These results have been repeated and confirmed by a series of evidence from Severe Asthma Research Program (SARP) (63,64). They consistently demonstrated that mixed granulocytic subtype is the most refractory inflammatory subtype, characterized by the lowest lung function, worse asthma control, increased symptoms, greater healthcare requirements, and further loss in lung function, suggesting cell to cell interaction or overlapping inflammatory pathways (63,64).…”
Section: Inflammatory Subtype and Future Maintenance Therapy/ Controlmentioning
confidence: 76%
“…Despite this, therapeutics specifically targeting neutrophils, even in patients with neutrophilic inflammation, have not shown efficacy ( 103 105 ). Given the common observation of combined increases in lung eosinophils and neutrophils with more severe disease, it is conceivable that targeting both cells may be more important ( 44 , 106 ).…”
Section: Integrating Clinical Molecular and Therapeutic Phenotypes To Understand Mechanismsmentioning
confidence: 94%
“…Longitudinal SARP data suggest that children with severe asthma, which is EOA by definition, may resolve their severe asthma, with high blood eosinophils being the best predictor of remission ( 13 ). Exacerbation-associated asthma, at least before T2 biologic intervention, appears to be a consistent characteristic of a poorly defined phenotype or poorly defined phenotypes, with baseline blood eosinophil concentrations, elevations of both eosinophils and neutrophils in sputum, and plasma IL-6 concentrations all being predictive of exacerbation-prone disease ( 40 , 44 ). Elevations in both sputum eosinophils and neutrophils have also been associated with greater lung-function decline ( 44 ).…”
Section: Clinical and Molecular Biomarkers And Phenotypingmentioning
confidence: 99%
“…Following the baseline and TA-response characterizations, some participants also came in during a subsequent exacerbation. The acute exacerbation visit was within 5 days of a subject reporting ≥2 days of increased symptoms compared with baseline and could occur any time after the subject had completed the baseline and post-TA visits and at least 6 weeks prior to the final visit [37], which was 36 months after baseline [38]. The recovery visit was 6 weeks after the acute exacerbation visit.…”
Section: Methodsmentioning
confidence: 99%